Oxytocin receptor signaling modulates novelty recognition but not social preference in zebrafish - Ribeiro, Diogo (2020)
Sociality is a complex phenomenon that involves the individual's motivation to approach their conspecifics, along with social cognitive functions that enable individuals to interact and survive. The nonapeptide oxytocin (OXT) is known to regulate sociality in many species. However, the role of OXT in specific aspects of sociality is still not well understood. In the present study we investigated the contribution of the OXT receptor (OXTR) signaling in two different aspects of zebrafish social behavior: social preference, by measuring their motivation to approach a shoal of conspecifics, and social recognition, by measuring their ability to discriminate between a novel and familiar fish, using a mutant zebrafish lacking a functional OXTR. Although oxtr mutant zebrafish displayed normal attraction to a shoal of conspecifics, they exhibited reduced social recognition. We further investigated if this effect would be social-domain specific by replacing conspecific fish by objects. Although no differences were observed in object approach, oxtr mutant fish also exhibited impaired object recognition. Our findings suggest that OXTR signaling regulates a more general memory recognition of familiar vs. novel entities, not only in social but also in a non-social domain, in zebrafish.